2015
DOI: 10.1063/1.4926365
|View full text |Cite
|
Sign up to set email alerts
|

Nonpolar III-nitride vertical-cavity surface-emitting lasers incorporating an ion implanted aperture

Abstract: We report on our recent progress in improving the performance of nonpolar III-nitride vertical-cavity surface-emitting lasers (VCSELs) by using an Al ion implanted aperture and employing a multi-layer electron-beam evaporated ITO intracavity contact. The use of an ion implanted aperture improves the lateral confinement over SiNx apertures by enabling a planar ITO design, while the multi-layer ITO contact minimizes scattering losses due to its epitaxially smooth morphology. The reported VCSEL has 10 QWs, with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
74
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(76 citation statements)
references
References 61 publications
1
74
0
Order By: Relevance
“…In GaAs-VCSELs simultaneous current and optical confinement is achieved by selective oxidation of a high Al-content AlGaAs-layer. Recently, new approaches for current confinement in GaN-VCSELs have been developed such as plasma damage of p-GaN 32 , ion implantation 36,47 , and airgaps by photoelectrochemical etching 38 . A number of key challenges in GaN-VCSEL will be described in more detail in the next chapter.…”
Section: State-of-the-artmentioning
confidence: 99%
See 1 more Smart Citation
“…In GaAs-VCSELs simultaneous current and optical confinement is achieved by selective oxidation of a high Al-content AlGaAs-layer. Recently, new approaches for current confinement in GaN-VCSELs have been developed such as plasma damage of p-GaN 32 , ion implantation 36,47 , and airgaps by photoelectrochemical etching 38 . A number of key challenges in GaN-VCSEL will be described in more detail in the next chapter.…”
Section: State-of-the-artmentioning
confidence: 99%
“…Publications from a few groups followed, and since the first demonstrations there have been a lot of progress in the field of electrically injected III-nitride based VCSELs, both in terms of new technological solutions as well as performance characteristics. 31 To date there are seven groups in the world who have demonstrated lasing under electrical injection [27][28][29][30][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] , and the different approaches and structures are summarized in Table 1. The performance characteristics of published devices, in terms of output power and threshold current density, are plotted in Fig.…”
Section: State-of-the-artmentioning
confidence: 99%
“…Recently, Leonard et al proposed an approach using ion-implantation to define the current aperture. In their result, the index contrast between the implanted and the non-implanted p ++ GaN can be enhanced to 0.05 [9]. In this letter, we propose an alternative design using self-aligned SiO 2 aperture featuring a low index and high resistance.…”
Section: Introductionmentioning
confidence: 99%
“…III-Nitride based materials are highly attractive for making vertical microcavity (MC) light emitters such as strongly coupled polariton lasers and conventional vertical-cavity surface-emitting lasers (VCSELs) due to their large exciton binding energies and wide spectra tuning range in the ultraviolet-visible region [1][2][3][4][5][6][7][8][9][10][11][12]. So far, electrically pumped polariton emitters and conventional VCSELs have been demonstrated in III-nitride based MCs at room temperature (RT).…”
Section: Introductionmentioning
confidence: 99%
“…High reflectivity distributed Bragg reflectors (DBR) structure, short cavity thickness [3][4][5] , high transparence conductive layer, efficient transverse current spreading, small current confinement aperture, and resonant cavity controled in the nitride VCSEL need to be improved. Leonard et al reported on violet nonpolar III-nitride VCSELs with a tunnel junction intracavity contact 6 and an Al ion implanted aperture 7 . The epitaxial AlGaN/GaN stack 8,9 and AlN/GaN stacks 10,11 structures had been reported for the bottom epitaxial DBRs in GaN-based VCSEL devices.…”
mentioning
confidence: 99%